MiR-18a-downregulated RORA inhibits the proliferation and tumorigenesis of glioma using the TNF-α-mediated NF-κB signaling pathway - Yang Jiang; Jinpeng Zhou; Junshuang Zhao; Dianqi Hou; Haiying Zhang; Long Li; Dan Zou; Jiangfeng Hu; Ye Zhang; Zhitao Jing (EBioMedicine, 2020)
Background: Glioma has a poor prognosis, and is the most common primary and lethal primary malignant tumor in the central nervous system. Retinoic acid receptor-related orphan receptor A (RORA) is a member of the ROR subfamily of orphan receptors and plays an anti-tumor role in several cancers. Methods: A cell viability assay, the Edu assay, neurosphere formation assay, and xenograft experiments were used to detect the proliferative abilities of glioma cell line, glioma stem cells (GSCs). Western blotting, ELISAs, and luciferase reporter assays were used to detect the presence of possible microRNAs. Findings: Our study found for the first time that RORA was expressed at low levels in gliomas, and was associated with a good prognosis. RORA overexpression inhibited the proliferation and tumorigenesis of glioma cell lines and GSCs via inhibiting the TNF-α mediated NF-κB signaling pathway. In addition, microRNA-18a had a promoting effect on gliomas, and was the possible reason for low RORA expression in gliomas. Interpretation: RORA may be a promising therapeutic target in the treatment of gliomas. Keywords: Glioma, Glioma stem cells, RORA, Tumorigenesis, microRNA-18a